Complexity : a very short introduction - Holland, John H. (John Henry), 1929- ([Oxford] : Oxford University Press, 2014)
In this very short introduction, John Holland presents an introduction to the science of complexity. Using examples from biology and economics, he shows how complexity science models the behaviour of complex systems.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 25, 2014).
Keywords: Complexity (Philosophy)